Mudrā Yoga Dalam Teks Hatha Yoga Pradipika Dan Gerandha Saṁhitā - Made G. Juniartha; Ni Ketut Anjani (Jurnal Yoga dan Kesehatan, 2023)
Hatha Yoga Pradipika and Gheranda Saṁhitā are very important guides to Hatha yoga. Swami Svatmaram (15th century CE) is the author of Hatha Yoga Pradipika. The text contains various practices of Hatha yoga in four chapters. Another text Gheranda Samhita (late 17th century) serves as an encyclopedia on Hatha yoga covering seven chapters. Various Hatha yoga practices have been combined in this text. In this article the author tries to present a general description of the practices in the two texts, especially regarding the discussion of mudrā yoga in a nutshell. This study was carried out systematically following the scientific method presented in literature review articles with the aim of explaining the types of mudrā found in the Hatha Yoga Pradipika and Gheranda Saṁhitā texts as well as the classification of mudrā and its use in hatha yoga practice. The types of mudrā found in the Hatha Yoga Pradipika text consist of 10 mudrā including; maha mudrā, maha bandha, maha vedha, khechari, uddiyana bandha, mula bandha, jalandhara bandha, viparita karani, vijroli and shakti chalana. Meanwhile, the types of mudrā found in the Gheranda Saṁhitā text consist of 25 mudrā, namely; maha mudrā, nabho mudrā, uddiyana, jalandhara, mulabhanda, mahabhanda, maha vedha, khecari, viparitha karani, yoni, vajroli, sakticalani, tadagi, manduki, sambhavi, pancadharana (five dharana), asvini, pasini, kaki, mature, bhujangini. Mudrā can be classified into 5 categories namely hasta mudrā, māna mudrā, kaya mudrā, bandha mudrā and adhara mudrā. Mudrā is useful for maintaining stability and balance of the body and mind can be focused on an object and the mind does not fluctuate.